Dostarlimab A new hope for endometrial cancer patients in Pakistan - Khan, Maliha (Journal of the Pakistan Medical Association, 2024)
Endometrial cancer (EC) is the most common gynaecological cancer in Pakistan, with an estimated incidence of 7.4 per 100,000 women [1]. It is a disease where cancer cells grow in the lining of the uterus (endometrium). EC can be classified into two types based on the genetic features of the cancer cells: mismatch repair deficient (dMMR) or microsatellite instability-high (MSI-H), and mismatch repair proficient (pMMR) or microsatellite stable (MSS). The former type accounts for about 20-30% of EC cases and has a worse prognosis than the latter [2]. Dostarlimab is a monoclonal antibody that blocks a protein called PD-1 on immune cells. The immune system is often restrained by PD-1, which stops it from targeting healthy cells. However, some cancer cells can exploit this mechanism by producing proteins (PD-L1 and PD-L2) that bind to PD-1 and switches off the immune response. By blocking PD-1, Dostarlimab restores the immune system’s ability to recognise and kill cancer cells [3]. Dostarlimab has been approved by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for the treatment of adults with dMMR/MSI-H recurrent or advanced EC that has progressed on or following prior treatment with a platinum-containing regimen [4,5]. Clinical studies have shown positive results for Dostarlimab in this patient population. In the GARNET trial, Dostarlimab achieved an objective response rate (ORR) of 43.5%, meaning that 43.5% of patients had their tumours shrink or disappear after treatment [3]. The median duration of response (DOR) was not reached, indicating that most responses persisted [8]. The most common side effects of Dostarlimab were fatigue, nausea, diarrhoea, anaemia, and constipation [5]. Dostarlimab offers new hope for endometrial cancer patients in Pakistan who have limited treatment options and poor outcomes. It is a targeted therapy that harnesses the power of the immune system to fight cancer. It is also a convenient and well-tolerated treatment that can be administered every 3 or 6 weeks as an intravenous infusion [2,3]. Dostarlimab is not yet available in Pakistan, but efforts are underway to bring it to the country as soon as possible. Dostarlimab has the potential to improve the quality of life and survival of endometrial cancer patients in Pakistan who have dMMR/MSI-H tumours.